Minecraft : heart of cobblestone Volume 1 - Clemson, Andrew (Comics writer) (Minecraft, 2024)
Farmer Cobb likes to keep his crops as neat as possible, but when neighbors eat his produce and villagers plant potatoes in his field he decides to get away from everyone and build a tall tower.